Evaluation of Prevalence and Type of Ponticulus Posticus Among Haryana Orthodontic Patients: A Digital Lateral Cephalometric Study - Roney S. Regi; Deepankar Bhatnagar; Mun Bhawni Bagga; Komal Yadav; Pinaki Kalita (Journal of Indian Academy of Oral Medicine and Radiology)
Objectives: The present study aimed to investigate the prevalence and type of ponticulus posticus (PP) in patients who reported for orthodontic treatment. Materials and Methods: In total, 346 lateral cephalograms were examined for the presence of PP, their respective types, gender predominance, and the prevalence of each type of PP in either gender. Data obtained were subjected to descriptive analysis. Results: PP had a prevalence rate of 20.52%, among which grades II, III, and IV represented 10.4%, 6.1%, and 4%, respectively. Females exhibited a slightly higher incidence (52.1%) than males (47.9%). Females represented a higher number of grade II and grade IV PP. Male patients displayed a higher incidence of grade III PP. The findings of gender predominance in each grade of PP were found to be statistically significant with P values < 0.05 level of significance at 95% confidence interval. Conclusion: PP was found to be a relatively common anomaly among the observed sample. Orthodontists, being directly and extensively involved in manipulating, enhancing, and restricting facial bone structures using functional and extraoral appliances, must be vigilant and concerned about any pathology affecting bone, such as that of PP.